A computational study on the three-dimensional printability of precipitate-strengthened nickel-based superalloys. (21st December 2018) - Basoalto, H. C.; Panwisawas, C.; Sovani, Y.; Anderson, M. J.; Turner, R. P.; Saunders, B.; Brooks, J. W.
Abstract : This paper presents a computational framework to study the differences in process-induced microvoid and precipitate distributions during selective laser melting (SLM) of two nickel-based superalloys representative of low (IN718) and high (CM247LC) volume fraction precipitate-strengthened alloys. Simulations indicate that CM247LC has a higher propensity to form process-induced microvoids than IN718. Particle sintering is predicted to be strongly influenced by the powder size distribution. For deposition thickness of approximately 40 μm, thermal gradients during cooling are predicted to be larger for CM247LC than IN718 and consequently expect the development of larger residual stresses for a high volume fraction γ ′ alloy. A coupled mean field/finite-element approach has been used to predict the precipitate distributions across a simple rectangular build and during a subsequent hot isostatic pressing (HIP) cycle. Unimodal and multi-modal particle distributions are predicted for IN718 and CM247LC at the end of the SLM, respectively. A higher volume fraction of γ ′ is predicted for CM247LC at the end of the SLM process. During HIP, simulations indicate a dramatic increase in the γ ′ volume fraction in CM247LC, which can result in a reduction in stress relaxation and lead to a ductility drop.